Zakazana samodzielność poznawcza: kształcenie początkowe pod przymusem rozumowania zapożyczonego - Klus-Stańska, Dorota (Studia Edukacyjne, 2023)
The article contains an analysis of the empirical material created during the internship of students’, future primary school teachers, as a result of their observations, followed by team analysis and gathering in portfolios. Observations were conducted for 6 weeks in 30 different schools, lasting 120 hours (60 hours of lessons typical for initial grades and 60 hours of English lessons). Fragments from portfolios devoted to the teaching methods that children are exposed to were selected for the study. Interpretive analysis of documents helped to indicate a very low status of pupils’ cognitive independence, blocking creative thinking, and preventing peer learning. The strength and persistence of this teaching model creates the risk of developing a habit of waiting for guidance on how to think and leading to a permanent inability to reason beyond that borrowed from others.